MODERNISASI PENGOLAHAN PAKAN BEBEK DENGAN MESIN PENGADUK DI PETERNAKAN TARET JAYA DESA AIR ANYIR KABUPATEN BANGKA - Saparin, Saparin; Wijianti, Eka Sari; Setiawan, Yudi; Suhdi, Suhdi; Rodiawan, Rodiawan; Ariksa, Jeri (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
Breeding ducks has several advantages, including: 1) the stages of raising ducks are easier; growth period; 2) duck growth is much faster, need 40 days to harvest; 3) marketing of meat and egg crops is easier; and 4) you can sell other parts to ducks, duck feathers for crafts and their droppings can be used as catfish feed. For laying ducks, their eggs can be harvested when they are 5 to 7 months old. Breeding ducks promises big enough profits that one of the livestock groups "Taret Jaya" has been raising broiler ducks since 2022. The community service partner is the Taret Jaya livestock group, located in Air Anyir village, Merawang sub-district, Bangka Regency. Based on the results of the survey to partner locations, there were several partner problems, including: manual counting of ingredients, limited knowledge of duck feed mixture ingredients, limited knowledge in making duck feed (fermentation process), and the mixing process in making feed was still manual. Currently, partners chop the feed ingredients using machetes and stir the feed ingredients using a hoe. The ingredients that have been stirred are then directly given to the ducks without going through a fermentation process. Through community service at this department level, the service team provides a solution that is offered in the form of a duck feed mixer machine. Mixing time with 50-60 kg of mixed material using a machine is 6 times faster than manually, namely around 5 minutes, compared to manual which takes 30 minutes. The service team has handed over to service partners, among other things: one unit of feed mixing machine, DOD duck seeds, feed making materials, and other supporting equipment for raising livestock. With this machine, partners can increase their livestock productivity.